Cognition and learning in diverse settings - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (Advances in learning and behavioral disabilities, 2005)
Essential to the treatment of learning and behavioral disabilities is an understanding of the cognitive processes brought into play in educational contexts, how they contribute to problems in learning and behavior, and how these processes might be ameliorated. Equally important is a careful consideration of the setting in which learning takes place, and how it ameliorates, or contributes to, learning and behavioral disorders. In this volume, the role of cognition in learning and behavioral disorders is considered along with investigation of learning in diverse settings, including clinical, special class, and inclusive general education classrooms. In this volume are chapters on such cognitive processes as working memory, spatial learning, and cognition in mathematics. In addition, learning is examined within a variety of setting arrangements, and considers such topics as the context of teacher-student relationships, co-teaching arrangements in inclusive instruction, issues in educational placement, clinically-based interventions for dyscalculia, collaborative teaching relationships in inclusive social studies teaching. This volume includes contributions from internationally recognized experts in the field of learning and behavioral disabilities. The book is intended for interested professionals and practitioners; researchers in learning and behavioral disabilities; and graduate students in psychology, education, and special education, particularly those concerned with the issues of cognition and learning in a variety of instructional contexts.